(untitled) (Superficies y Vacío, 2020)
The need for fast and affordable portable detection systems, which are highly sensitive to organic molecules, has directed the development of devices based on SERS effect (Surface-Enhanced Raman Spectroscopy). In the present study, the green synthesis of Au nanoparticles assisted with Cymbopogon citratus and Citrus paradisi aqueous extract is reported, which are obtained with star-like and triangular shapes, respectively, as well as the chemical synthesis of cubic Ag nanoparticles. The nanostructures were characterized with UV-Vis spectroscopy and Transmission Electron Microscopy. The Ag and Au nanostructures were deposited on a ribbed polystyrene surface, to evaluate these arrays as active substrates for SERS using methylene blue as target molecule. An improvement in the characteristic Raman signals of methylene blue was observed in all cases, especially when Au nanostructures with star-like morphology are employed.